Talent development for youth entrepreneurship - Din, Badariah; Mohd Khan, Shazida Jan; Mansor, Mohd Najib (UUM Press, 2020)
This book highlights the issues and challenges faced by youth in nurturing their entrepreneurial mind-set to start-up and sustain a business. Specifically, the Talent Development for Youth Entrepreneurship book captures views on the issues of entrepreneurial engagement among youth in Malaysia, social and cultural attitude towards youth entrepreneurship, entrepreneurship education program me, business support, including physical infrastructure, regulatory framework conditions, access to finance or to start-up financing and skills mismatch faced by entrepreneurs